2007
DOI: 10.1200/jco.2006.09.4474
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Proliferation Signature Related to Survival in Nodal Peripheral T-Cell Lymphomas

Abstract: Our findings indicate that proliferation could be an important factor in evaluating nodal PTCL outcome and may help to define a more aggressive phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 37 publications
(16 reference statements)
7
59
2
2
Order By: Relevance
“…Two years later, our group refined this scoring system by substituting Ki67 expression for bone marrow involvement (3), which allowed for the identification of three distinct subgroups of patients with clearly different clinical behavior. Remarkably, the proposed score considered for the first time a biological parameter (the proliferative index), consistent with the observation made later by Cuadros et al that a gene signature related to proliferation heralds a poor prognosis (70). Interestingly, we also found in a univariate analysis that EBV positivity and cytotoxic marker expression were adverse prognostic indicators (3).…”
Section: Prognosissupporting
confidence: 90%
“…Two years later, our group refined this scoring system by substituting Ki67 expression for bone marrow involvement (3), which allowed for the identification of three distinct subgroups of patients with clearly different clinical behavior. Remarkably, the proposed score considered for the first time a biological parameter (the proliferative index), consistent with the observation made later by Cuadros et al that a gene signature related to proliferation heralds a poor prognosis (70). Interestingly, we also found in a univariate analysis that EBV positivity and cytotoxic marker expression were adverse prognostic indicators (3).…”
Section: Prognosissupporting
confidence: 90%
“…Moreover, C-MYC overexpression is known to be related to a high proliferation index and poor clinical outcome in ALCL. 9 Cuadros et al 10 identified a poor prognosis signature related to proliferation using gene expression studies. Went et al…”
mentioning
confidence: 99%
“…Certains profils semblent corrélés à la survie des patients : la surexpression de la voie NFB est associée à un bon pronostic [38], contrairement à la surexpression d'une signature de prolifération qui, elle, est de mauvais pronostic [39]. On distingue plusieurs sous-entités de LTP-NS.…”
Section: Synthèse Revuesunclassified